Making Morris (Fe)Male: Gender and Dancing Bodies - Greenhill, Pauline (Ethnologies, 1997)
Morris dancing has historically been viewed by its scholars as an “English male dance tradition.” Each of these descriptors can be deconstructed, but this article focuses primarily upon understanding how Morris has been gendered male, and the effects such gendering has upon actual dancers and how they understand their practice.